1999
DOI: 10.1080/01421599978979
|View full text |Cite
|
Sign up to set email alerts
|

BEME Guide No. 2: Teaching and learning communication skills in medicine-a review with quality grading of articles

Abstract: A literature search for articles concerning communication skills teaching and learning in medicine was done.The search yielded 180 pertinent articles, which were quality graded into the three categories of high, medium and low quality, using established criteria. Only those of high and medium quality were used for the review, which thus is based on 31 randomized studies, 38 open effect studies and 14 descriptive studies. Communication skills can be taught in courses, are learnt, but are easily forgotten if not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
332
3
55

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 475 publications
(407 citation statements)
references
References 2 publications
11
332
3
55
Order By: Relevance
“…The educational intervention in our study was shown to be effective training methods for helping doctors acquire some communication skills such as 'active listening and facilitating patients' response' and 'understanding patient's perspective' that have been used in both undergraduate and postgraduate teaching (Kurtz et al 1998;Aspegren 1999;Maguire & Pitceathly 2002). However, other skills such as 'initiating a session' or 'closure' were not shown to be better with participation in the intervention group.…”
Section: Summary Of Main Findingsmentioning
confidence: 60%
“…The educational intervention in our study was shown to be effective training methods for helping doctors acquire some communication skills such as 'active listening and facilitating patients' response' and 'understanding patient's perspective' that have been used in both undergraduate and postgraduate teaching (Kurtz et al 1998;Aspegren 1999;Maguire & Pitceathly 2002). However, other skills such as 'initiating a session' or 'closure' were not shown to be better with participation in the intervention group.…”
Section: Summary Of Main Findingsmentioning
confidence: 60%
“…This is in line with the overwhelming evidence in the international literature on the teaching of communication skills. 9,10 However, Coulehan and Williams refer to other values and virtues related to soft skills, namely empathy, compassion, attentiveness, fidelity and courage, that can neither be taught easily nor developed 'in a clinical factory'. 11 For the development of soft skills, teaching approaches that focus on experiential learning -'if you watch someone else' or 'actually doing it' -are more effective than the acquisition of facts.…”
Section: Teaching and Learning Soft Skillsmentioning
confidence: 99%
“…Dans le curriculum actuel des Ă©tudes de mĂ©decine de la facultĂ© de biologie et de mĂ©decine de Lausanne, l'une des approches de l'enseignement des habiletĂ©s Ă  la communication mĂ©decin-malade repose sur un dispositif d'enseignement en petits Le dispositif d'enseignement et le contexte, c'est-Ă -dire le recours Ă  un patient simulĂ©, les scĂ©narios prĂ©sentĂ©s, l'utilisation de la vidĂ©o et la discussion de groupe montrent que les Ă©tudiants, qu'ils soient actifs ou observateurs, ont le sentiment d'apprendre tant sur le plan de savoir-faire et du savoir-ĂȘtre que sur le plan de la dynamique relationnelle. Ceci confirme les rĂ©sultats d'autres travaux 9,10,11,19 . Dans l'interprĂ©tation des rĂ©sultats, il faut toutefois se souvenir que notre Ă©tude s'est limitĂ©e Ă  demander aux Ă©tudiants d'apprĂ©cier les bĂ©nĂ©fices qu'ils retirent de cet enseignement, ce qui ne permet pas d'objectiver l'impact de cet enseignement sur les habiletĂ©s de communication des Ă©tu-diants.…”
Section: Discussionunclassified
“…Les habiletĂ©s de communication peuvent ĂȘtre enseignĂ©es de diffĂ©rentes maniĂšres. Cependant, les mĂ©thodes d'enseignement de type « expĂ©rientiel » (experiential) ont tendance Ă  ĂȘtre les plus efficaces 9,10 et les plus apprĂ©ciĂ©es des Ă©tudiants 11 . L'utilisation de patients simulĂ©s dans l'enseignement mĂ©dical, et plus particuliĂšrement dans l'entraĂźnement Ă  la communication mĂ©decin-malade, est une pratique rĂ©pan-due qui offre de nombreux avantages 12 .…”
Section: Introductionunclassified